Beauty and ugliness as endocrine pathology: a look through the prism of history and art - Kseniya O. Samsonova (LLC "MEDIAFORMAT", 2023)
Throughout history, people have reacted differently to various physical abnormalities that develop in the absence of treatment and progression of diseases of the endocrine system. From antiquity until relatively recently, some manifestations of endocrine pathology caused fear and horror, while others, on the contrary, were considered ideals of beauty. But, thanks to the improvement of diagnostic and treatment methods, it is now increasingly rare to find gross long-term consequences of diseases, the owners of which a century ago would have been doomed to a difficult and not always long life. All this remains on the pages of history and in the works of masters, which can be an excellent tool for young professionals.